Time - Frequency Analysis of Narrow Bipolar Pulses observed in Sri Lanka - L Gunasekara; A. Vayanganie; S Jayalal; M Fernando; U Sonnadara; V Cooray (ICLP, 2016)
Narrow Bipolar Pulses (NBP) of a single thunderstorm from a coastal location in Sri Lanka were subjected to S-transformation in order to study their timefrequency information. This study is an extension to a similar study carried out by the authors where properties of NBPs were analyzed using the wavelet transformation. Keeping in line with the previous study, 18 events pertaining to equal number of positive and negative NBPs with the narrowest temporal widths were studied. The data was obtained from the southern coastal area of Sri Lanka (Matara - 5.950 N, 8.530 E) from a highly active thunderstorm, which occurred during the month of May in 2013. The waveforms were recorded with a 10 ns resolution within a 100 ms time window. The spanning (width) and the ratio of peak power amongst the initial and overshoot pulses were measured and compared for each polarity. The negative NBPs had an average spanning of 134 - 371 kHz. The overshoot of the same had an average range of 127 - 255 kHz. The positive NBPs had an average spanning of 103 - 245 kHz. The overshoot of the same had an average range of 102 - 195 kHz. The ratio of peak power of NBPs to overshoot had an average of 1.08 for both positive and negative pulses. The spectrogram reveals the initial and overshoots pulses to be relatively equal in power intensities.